2009
DOI: 10.1016/j.clinph.2009.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Rostral anterior cingulate cortex theta current density and response to antidepressants and placebo in major depression

Abstract: Objective To assess whether pretreatment theta current density in the rostral anterior cingulate (rACC) and medial orbitofrontal cortex (mOFC) differentiates responders from non-responders to antidepressant medication or placebo in a double-blinded study. Methods Pretreatment EEGs were collected from 72 subjects with Major Depressive Disorder (MDD) who participated in one of three placebo-controlled trials. Subjects were randomized to receive treatment with fluoxetine, venlafaxine, or placebo. Low-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 40 publications
4
116
1
Order By: Relevance
“…This suggests these two types of theta activity could have different implications and different origins. In line with Spronk et al [109], several studies have indeed shown low theta activity localized to the ACC, as estimated by source localization techniques, to respond worse to various antidepressant treatments [110,111,112,113]. These findings are in line with positron emission tomography and functional magnetic resonance imaging studies demonstrating low metabolic activity in the ACC is associated with worse treatment outcome; see also Pizzagalli [114] for an excellent review and meta-analysis on the rostral ACC (rACC) and treatment outcome.…”
Section: Biomarkerssupporting
confidence: 65%
“…This suggests these two types of theta activity could have different implications and different origins. In line with Spronk et al [109], several studies have indeed shown low theta activity localized to the ACC, as estimated by source localization techniques, to respond worse to various antidepressant treatments [110,111,112,113]. These findings are in line with positron emission tomography and functional magnetic resonance imaging studies demonstrating low metabolic activity in the ACC is associated with worse treatment outcome; see also Pizzagalli [114] for an excellent review and meta-analysis on the rostral ACC (rACC) and treatment outcome.…”
Section: Biomarkerssupporting
confidence: 65%
“…More specifically, the major depression symptom of anhedonia, characterized by reward-insensitive behavior and blunted positive emotionality -and hence, apparently, the extremely low end of aE (Depue, 1995) -has been associated with abnormally low levels of activity in the ventral-rostral ACC (rACC) regions (Pizzagalli, Peccoralo, Davidson, & Cohen, 2006) and with blunted nucleus accumbens responses to reward signals (Wacker, Dillon, & Pizzagalli, 2009). Furthermore, pharmacological challenge studies have demonstrated that the ACC responds to dopaminergic drugs (e.g., Völlm et al, 2004), and ACC activity also qualifies as a predictor for psychopharmacological treatment responses (for selective norepinephrine and serotonin reuptake inhibitors, see Korb, Hunter, Cook, & Leuchter, 2009).…”
Section: Agentic Extraversion and Anterior Cingulate Cortex Activitymentioning
confidence: 99%
“…Responders had greater pretreatment theta activity (6.5-8 Hz), again localized by LORETA to the rACC when compared to nonresponders and there was a significant correlation of pretreatment theta and improvement in depression after treatment, which replicates the findings of Pizzagalli et al (2001). In the first double-blind, placebo controlled study to examine the relationship of pretreatment EEG and antidepressant response, Korb et al (2009) used LORETA to localize theta activity (4-7 Hz) to the same rACC region as specified by Pizzagalli et al (2001). Patients who responded to either fluoxetine or venlafaxine (n=22) had greater theta than nonresponders (n=15), whereas there was no difference between placebo responders (n=15) and nonresponders.…”
Section: Loreta Measures Of Theta and Treatment Responsementioning
confidence: 56%